Il "valore" del campione: uno sguardo sociologico sulla figura del calciatore contemporaneo- Schottè, M. (2021). La valeur du footballer, Paris: CNRS Editions - Giovannipaolo Ferrari (SHARE Press, 2023)
This article delves into a sociological analysis of the book "La valeur du footballer" of Manuel Schottè, examining the attributed value of football players and the prevalent trend in the soccer world to emphasize individuality over the collective. The author explores interpretations by considering the valorization as a historical product rooted in structural dynamics and context-specific practices. The article further explores football as a space for constructing a status of prominence, the valorization of a minority of players as a symbolic frontier, concentration and circularity of profits, and the individualization of performance and player valorization. Ultimately, the work provides a comprehensive perspective connecting history, social structure, and contemporary dynamics to comprehend the value within football.